Mergers and Financial Performance of Access Bank Plc in Nigeria - Oziegbe, David Jerry; Monday , Daniel Daniel; Obasuyi, Maxwell Ogbemudia; Okoh, Ifunanyachukwu Jennifer (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study examined the impact of mergers and acquisition on the financial performance of merged banks in Nigeria. Specifically, the study aimed to investigate the impact of the merger between Access bank Plc and Diamond Bank Plc on financial performance. The merger period was classified into (2016 to 2019) and (2020 to 2023). Secondary data was obtained from the annual reports of Access Bank plc for the period under review. The t-test statistic was used to determine if there is a significant difference in the financial performance of Access bank pre-merger and the post-merger. The findings revealed that there was a significant difference in the financial performance (ROE, ROA, CAR). Based on the findings, the study concludes that mergers and acquisition affect the overall performance of banks. The study therefore recommend that merger and acquisition is a strategy that banks should adopt to improve their financial performance.